Numerical study of the Marangoni effect induced by soluble surfactants and solute based on rising droplets - Mao, Qi; Yang, Qing-Jun; Li, Yu-Long; Cao, Wang (Physics of fluids (1994), 2024)
In this study, we present a numerical investigation into the phenomenon of rising droplets in immiscible fluids, focusing on the Marangoni effect induced by both solute and a combination of solute and soluble surfactants. We meticulously examine the interfacial behaviors of pure solute droplets and mixed droplets, with a particular interest on the intricate interplay among interfacial concentration, interfacial tension, Marangoni stress, and Marangoni convection. Our investigation provides insight into the influence of key physicochemical parameters, such as viscosity, diffusion coefficient, partition coefficient, and interfacial tension gradient, on the Marangoni instability. Furthermore, we conduct a comprehensive parametric exploration of the impact of dimensionless numbers such as the Langmuir number (La), the Damkohler number (Da), the Peclet number (Pe), and the elasticity number β on the stabilizing efficacy of surfactants. The research findings underscore the effectiveness of our numerical method in capturing the distinctive two-step acceleration characteristics of pure solute droplets and the stabilizing effect of surfactants on mixed droplets. Notably, our study reveals that the Marangoni instability may manifest even when the viscosity and diffusivity ratios of the two-phase fluids are closely matched. Partition coefficients below unity exhibit only a marginal influence on the re-acceleration time of the droplets. Systems characterized by extremely low interfacial tension gradients tend to exhibit no Marangoni instability. Moreover, an increase in La enhances the stability of mixed droplets, while a significant threshold is identified for Da to affect the stability of mixed droplets. The ascent speed of mixed droplets displays pronounced variation across varying Pe magnitudes. Finally, in scenarios involving a wide-ranging variation in β, mixed droplets transition between the states of pure solute droplets and rigid spheres, revealing a distinct-state transition point.